Immunogenicity and protective efficacy of recombinant Bacille Calmette-Guerin strains expressing mycobacterium antigens Ag85A, CFP10, ESAT-6, GM-CSF and IL-12p70 - Fu-Ying Dai; Jun-Fang Wang; Xue-Li Gong; Lang Bao (Taylor & Francis Group, 2017)
Objective: This study aimed to evaluate the immunogenicity and protective efficacy of recombinant bacille calmette-guerin (rBCG) strains expressing Ag85A (A), CFP10 (C), ESAT6 (E), IL-12p70 (I), and fusion protein GM-CSF (G). Method: rBCGs were established by integrating of A, C, E, I, G, AE, CE, IE, GC, GE and GCE into Mycobacterium bovis BCG-1173 and BCG-SH. The macro-effects of rBCGs on mice were evaluated by phenotype and weight. The immunogenicity of rBCGs was analyzed by lgG, lgG1 and lgG2a antibody titers, and IFN-γ and IL-4 contents through Enzyme-linked immunosorbent assay (ELISA). Meanwhile, the proportions of CD4+ and CD8+ T splenic lymphocytes were determined using flow cytometry. The protective efficacy of rBCGs was evaluated by bacterial load in spleen and lung tissues from immunized mice. Results: rBCGs exhibited no obvious side effects on mice. The antibody titers of lgG, lgG1 and lgG2a, proportion of CD4+ and CD8+ T cells, and concentrations of IFN-γ were found to be significantly higher in multiple-gene rBCGs than that in single-gene rBCGs (P < 0.05). Bacterial load in both spleen and lung tissues from mice infected with M. tuberculosis H37Rv were significantly reduced by rBCGs. A significantly lower bacterial load was revealed in rBCG-1173:A compared with multiple-gene rBCGs (P < 0.05). Conclusion: Immunogenicity was better on multiple-gene rBCGs than on single-gene rBCGs, while excellent protective efficacy was exhibited on rBCG-1173:A and BCG-1173.